Perbandingan Hasil Pengelompokan Menggunakan Metode Self Organizing Maps dan Metode Average Linkage (Studi Kasus: Data PDRB tiap provinsi di Indonesia) - Gabriella Haumahu (Tensor: Pure and Applied Mathematics Journal, 2020)
Gross domestic regional product (GDRP) is one of important indicators that can be used to determine economic conditions in some areas. This makes GDRP is very interesting to be studied. In this paper we cluster 33 provinces in Indonesia based on GDRP in 2013. We use self organizing and average linkage method of cluster analysis to investigate it. We also compare the results of both methods. We found that Average linkage method has better performance than self organizing method because it has smaller rasio.